NICKI MINAJS COMMENTS IN AMERICAN IDOL SEASON 12: AN ANALYSIS OF WOMENS LANGUAGE FEATURES - Diana Chandra; Made Frida Yulia (Sanata Dharma University, 2018)
Women are believed to speak differently from men. They carry certain features which are distinctive in their speech (Lakoff, 2004). However, some women are found to speak differently from womens speech in general. This phenomenon is reflected in the use of language by Nicki Minaj, one of the judges of American Idol Season 12, whose speech stands out above the rest of the other women. The study investigates Nicki Minajs comments in American Idol Season 12 in terms of womens language features. It focuses on two issues, namely how the language used by Nicki Minaj in American Idol Season 12 conforms to womens language features and what possible factors cause the absence of womens language features in Nicki Minajs comments to the contestants of American Idol Season 12. To find answers to the two questions, document analysis was employed, in which seven videos of live performances taken from American Idol Season 12 were examined. The findings revealed that womens language features which appeared in Nicki Minajs comments were intensifier, emphatic stress, filler, rising intonation, and lexical hedge. The rest of the features did not appear in her speech; they were tag question, empty adjective, precise colour term, hypercorrect grammar, superpolite form, and avoidance of strong swear words. This phenomenon can be accounted for by four possible factors that cause their absence in Nicki Minajs comments to the contestants of American Idol Season 12. They were fathers speech, ethnicity, community of practice, and different social psychological perceptions.